Answer:
Step-by-step explanation:
f(-7) = 5(-7) - 3 = -35 - 3 = -38
Answer:
B.
Step-by-step explanation:
hope it helps :)
The result you get when you divide is 11 + 16/x + 1
(−2)³ = (-2)(-2)(-2)
Note that:
two negative numbers multiplied together results in a positive
one negative and one positive number multiplied results in a negative
Multiply:
(-2)(-2) = 4
4(-2) = -8
-8 is your answer
hope this helps
Answer:
Square pyramid
Step-by-step explanation:
The flat square on the bottom is 1 face and there are 4 triangle faces.
The flat square on the bottom has 4 vertices and there is the pointy 1 at the top that holds the 4 triangles.
Hope dis helps,
Have a great day.